Universidade, cidade e escola na formação para a cidadania: o ensino do direito tributário no ensino fundamental - Alcantara, Silvano Alves (2024)
This work deals with the imperative need for the Brazilian population, from a young age, to know Brazilian tax legislation in a didactic, motivating and transformative way, taking into account the current complexity of the matter and the way in which it is, or is no longer be presented to children and young people studying in elementary school. Thus, the problem identified in the research seeks to answer whether, and how, it is possible to teach Brazilian tax law institutes in basic education and, in particular, to elementary school students through not only formal education, but also non-formal education. and informal? That said, the objective of this work is to discuss and analyze the most varied stages contained in a project that deals with the process of creating and developing an educational product intended to fill the existing gap in basic education, that is, the teaching of tax law in the elementary School. The research made use of a systematic literature review (RSL), documentary research, as well as the construction of a prototype that sought to create a scenario of immersion of the learner in the context of experiences in the city and in direct contact with the institutes of tax law, which became an educational product. Based on the analysis, prototyping and preparation of an execution schedule, it was possible to develop and implement a tax education workshop, which was later embodied in a study guide. The RSL results show us that, with a few exceptions, academic production dedicated to the topic is scarce, given that it is still limited when analyzing the intersection between tax law and teaching in elementary school grades. Finally, it is concluded that the application of the tax education workshop was able to mobilize and stimulate the active participation of learners in contact with some tax law institutes, such as ICMS, IPVA and IPTU, making possible the understanding of these institutes, the starting from everyday life in cities, through experiences, consumer relations and the construction of elementary notions of citizenship.